2015
DOI: 10.1080/10941665.2015.1013143
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Relationships among Motivation, Service Quality and Loyalty: The case of the National Museum of Natural Science

Abstract: This study explores causal relationships between push and pull motivations, perceptions of service quality and loyalty intention, and examines the moderating role of membership status in the National Museum of Natural Science (NMNS), the largest museum in Taiwan. Data were collected from 405 paid admission visitors, with a quota and systematic sampling, from two stages of pre-and post-visit corresponding with twoquestionnaires. The results demonstrate that push and pull motivations impact on service quality pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 79 publications
(70 reference statements)
1
20
0
2
Order By: Relevance
“…Upgrading and updating various service facilities can create a good visiting environment [54]. Lighting and color are two important factors that influence the design effect of museum displays [7,[64][65][66]. Light not only improves the brightness of a room, but also combines the colors of the exhibits.…”
Section: Discussionmentioning
confidence: 99%
“…Upgrading and updating various service facilities can create a good visiting environment [54]. Lighting and color are two important factors that influence the design effect of museum displays [7,[64][65][66]. Light not only improves the brightness of a room, but also combines the colors of the exhibits.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it was found that tourist motivation played a moderating role on the relationship between tourist's experience and perceived quality. These findings could provide managers of historic and cultural destinations with guidance for better understanding visitors' experience, their motivation, and how they influence visitors' perception of service quality provided, which will in turn affect tourist' satisfaction and their behavioral intentions regarding future visits (Hsieh, Park, & Hitchcock, 2015;Hsieh et al, 2018;Yoon & Uysal, 2005).…”
Section: Discussionmentioning
confidence: 96%
“…HISTOQUAL was established to investigate perceived quality in the cultural and heritage tourism context (Chen & Shi, 2008). And MUSEQUAL was developed to assess museum visitor's experience of service and their satisfaction (Hsieh, Park, & Hitchcock, 2015).…”
Section: Perceived Qualitymentioning
confidence: 99%
“…The perceived quality of a museum is defined as the discrepancy between the museum visitors' initial expectations and the feelings experienced from a museum service provider. Perceived quality has been investigated by various service industries as it enables retention of the relationship with customers, attracts new customers, decreases costs, increases profits, improves corporate image, and engenders positive recommendations [20]. Perceived quality is formed on the basis of technical, functional, and environmental qualities, and it is perceived by the outcome, the process-creating outcome, and the physical environment of the service.…”
Section: Csr and Museum Perceived Quality Image And Reputationmentioning
confidence: 99%